Task-based estimation of past exposures to 60-hertz magnetic and electric fields at an electrical utility - Deadman, J.-E.; Church, G.; Bradley, C.; Armstrong, B. G.; Thériault, G. (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'Past exposures of electric utility workers to extremely low-frequency (ELF) magnetic (B) and electric fields (E) in Québec were estimated. Methods The current intensities were measured and durations of exposures determined for tasks or work locations in 14 job categories. Past task or location intensities were extrapolated from the present on the basis of interviews with long-term workers and utility personnel. Past task or location durations were estimated for the long-term workers. Time-weighted average (TWA) exposures for past periods were reconstructed for jobs from the intensity and duration estimates. Results Magnetic fields were estimated to have increased the most over time for substation and distribution-line jobs. Magnetic field exposures for jobs in the generation and transmission of electricity were estimated to have increased very little. For substation jobs, the ratios of magnetic fields in 1945 to those in 1990 ranged from 0.42 to 0.69; the corresponding figures for distribution-line jobs ranged from 0.36 to 0.94. For electric fields in substations, the estimated increase over time was less than for magnetic fields, the 1945:1990 ratios ranging from 0.59 to 0.88. For the distribution line jobs, the 1945:1990 ratios for electric fields were less than 1.0 in 4 cases (0.6 to 0.89), more than 1.0 in 3 others (1.13 to 2.01) and unchanged in 1. Conclusion Reconstruction of TWA exposures allowed changes in the intensity and the duration of exposures to be considered separately. Documentation of the intensity and duration of exposures for different tasks allows exposure reconstruction for jobs that have ceased to exist. The method is applicable elsewhere if exposure monitoring records allow the level and duration of exposures for tasks or locations to be calculated and if estimates of past durations and intensities of exposures can be reliably obtained.
Keywords: electric fields; electrical utilities; extremely low frequency; magnetic fields; retrospective exposure estimation